How nutrient rich are decaying cocoa pod husks? The kinetics of nutrient leaching - Hougni, D.G.; Schut, Antonius G.T.; Woittiez, Lotte Suzanne; Vanlauwe, Bernard; Giller, Kenneth E. (Springer, 2021)
Aim Recycling of cocoa pod husks has potential to contribute to mineral nutrition of cocoa. Yet little is known of the nutrient content and nutrient release patterns from the husks. The potassium (K) rich husks are usually left in heaps in cocoa plantations in Africa. We aimed to understand and quantify release patterns of K and other nutrients from husks under varying rainfall regimes and assessed the effects of partial decomposition and inundation on nutrient leaching rates.